Observation of Chinese Hamster Ovary Cells retained inside the non-woven fiber matrix of the CellTank bioreactor - Ye Zhang; Véronique Chotteau (Data in Brief, 2015)
This data article shows how the recombinant Chinese Hamster Ovary (CHO) cells are located in the interstices of the matrix fibers of a CellTank bioreactor after completion of a perfusion culture, supporting the article entitled “Very high cell density perfusion of CHO cells anchored in a non-woven matrix-based bioreactor” by Zhang et al. [1]. It provides a visualization of the cell distribution in the non-woven fiber matrix in a deeper view.